THE EFFECTIVENESS OF GROUP GUIDANCE WITH THE TECHNIQUE OF OVERCOMING RESISTANCE TO CHANGE IN IMPROVING THE SELF-EFFICACY OF PART-TIME WORKING STUDENTS - Nurhaida Nurhaida; Alfin Siregar (LP2M IAI Al-Khairat Pamekasan, 2025)
The purpose of this research is to assess the effectiveness of group counseling services using the Overcoming Resistance To Change technique to improve the self-efficacy of students at SMA Negeri 4 Tanjung Balai. The researcher employed a quantitative approach with a quasi-experimental research type, specifically using a pretest-posttest control Group design. The population consists of all 11th-grade students at SMA Negeri 4 Tanjung Balai, totaling 84 students, with a sample size of 16 students: 8 students in the experimental group and 8 students in the control group, who have low self-efficacy. The sampling method used is non-probability sampling, specifically purposive sampling. Data collection was conducted using a self-efficacy scale. The data analysis technique used is the t-test with the help of SPSS version 25, yielding a sig (2-tailed) value of 0.000 < 0.05. The output for pair 1 shows a thitung value of 27.693 with a Sig value of 0.000 (2-tailed) < 0.005. Meanwhile, the output for pair 2 shows a Sig value of 14.095 and a sig value of 0.000. The sig value of 0.000 < 0.005 indicates that Ha is accepted and Ho is rejected. This shows that the experimental class using group guidance services with the Overcoming Resistance To Change technique is effective in increasing the Self Efficacy of students who work part-time at SMA Negeri 4 Tanjung Balai.